Alih Teknologi Teknik Pewarnaan Menggunakan Antosianin Berbasis Ph Untuk Kain Tenun Khas Lombok - Dhony Hermanto; Nurul Ismillayli; Baiq Handayani Rinuastuti; Ulul Khairi Zuryati; Handa Muliasari; Qurnia Aini; Bela Azkiana; Ni Kadek Intan Wulan Sinta Dewi (Universitas Mataram, 2022)
Dyeing woven yarn using natural dyes is increasingly popular, but the process is complicated, color consistency is low, fades easily and color choices are limited. Service activities in Sukarara Village in the form of socialization and assistance on coloring techniques using pH-based anthocyanins (acidity degrees) were carried out as a solution to these problems. By varying the pH of the anthocyanin solution using buffer 2-10 followed by fixation/mordanting, more color variations (one type of plant extract), consistency and color resistance were achieved. The activity partners are 20 members of the Subahnale Tourism Awareness Group (Pokdarwis). Activities include FGD, interviews, socialization, mentoring and evaluation. The activity was carried out well without significant obstacles with an increase in the average value of partners from 55 to 87. It is hoped that Pokdarwis can synergize with the village government for the sustainability of activities so that the role of woven fabrics positively contributes to the community welfare.